The Germ Cell Determinant Blimp1 Is Not Required for Derivation of Pluripotent Stem Cells - Bao, Siqin; Leitch, Harry G.; Gillich, Astrid; Nichols, Jennifer; Tang, Fuchou; Kim, Shinseog; Lee, Caroline; Zwaka, Thomas; Li, Xihe; Surani, M. Azim (Cell stem cell, 2012)
Blimp1 (Prdm1), the key determinant of primordial germ cells (PGCs), plays a combinatorial role with Prdm14 during PGC specification from postimplantation epiblast cells. They together initiate epigenetic reprogramming in early germ cells toward an underlying pluripotent state, which is equivalent to embryonic stem cells (ESCs). Whereas Prdm14 alone can promote reprogramming and is important for the propagation of the pluripotent state, it is not known whether Blimp1 is similarly involved. By using a genetic approach, we demonstrate that Blimp1 is dispensable for the derivation and maintenance of ESCs and postimplantation epiblast stem cells (epiSCs). Notably, Blimp1 is also dispensable for reprogramming epiSCs to ESCs. Thus, although Blimp1 is obligatory for PGC specification, it is not required for the reversion of epiSCs to ESCs and for their maintenance thereafter. This study suggests that reprogramming, including that of somatic cells to ESCs, may not entail an obligatory route through a Blimp1-positive PGC-like state. [Display omitted] ► Knockout of Blimp1 has no effect on derivation or maintenance of ESCs or epiSCs ► Blimp1 is not required for reversion of epiSCs to an ESC state ► Blimp1 is required for PGC specification ► Transit through a PGC state is not obligatory for acquisition of pluripotency Bao et al. demonstrate that the key determinant of primordial germ cells (PGCs) Blimp1 is dispensable for the derivation of embryonic stem cells (ESCs) and epiblast stem cells (epiSCs) and for reprogramming. This suggests that acquisition of pluripotency does not entail an obligatory route through a Blimp1-positive PGC-like state.